Was Kos a member of the Second Athenian Naval Confederacy? - Sebők, Attila (Sapiens ubique civis, 2023)
After the defeat she suffered in the Peloponnesian War (431–404 BC), Athens worked on the restoration of her pre-war position in the diplomatic scenery of Hellas. One major portion of this process was the creation of the Second Athenian Confederacy. Possibly the most important conflict in the history of the Confederacy was the so-called Social War between 357 and 355 BC. In this conflict, some members of the Confederacy (namely Rhodes, Chios, Byzantium, and possibly Kos) waged war against Athens in order to leave the Confederacy. The participation of Kos as a rebel is argued against by Sherwin-White and some other scholars, assuming that only Rodes, Chios, and Byzantion revolted, but there is the possibility that there could have been more rebels, supported by Buckler, who collected the names of twelve states and could have revolted. In my study, I present an examination of the question of Kos and possible other rebels.